Trends, correlates, and survival of infants with congenital diaphragmatic hernia and its subtypes. Issue 14 (6th August 2018) - Ramakrishnan, Rema; Salemi, Jason L.; Stuart, Amy L.; Chen, Henian; O'Rourke, Kathleen; Obican, Sarah; Kirby, Russell S.
Abstract : Objective: To identify the live‐birth prevalence, trends, correlates, and neonatal and 1‐year survival rates of congenital diaphragmatic hernia. Methods: Using a population‐based, retrospective cohort study design, we examined 1, 025 cases of congenital diaphragmatic hernia from the 1998–2012 Florida Birth Defects Registry. We used Poisson and joinpoint regression models to compute prevalence ratios and temporal trends, respectively. Kaplan–Meier survival curves and Cox proportional hazards regression were used to describe neonatal and 1‐year survival and estimate hazard ratios representing the predictors of infant survival. Results: The birth prevalence of congenital diaphragmatic hernia was 3.19 per 10, 000 live births (95% confidence interval [CI]: 3.00–3.39); there was a 4.2% yearly increase among multiple cases only. Among all cases, maternal education less than high school (prevalence ratio: 1.25, 95% CI: 1.02–1.53), high school/associate degree/GED (prevalence ratio: 1.15, 95% CI: 1.01–1.32), multiple birth (prevalence ratio: 1.38, 95% CI: 1.05–1.81), and male sex (prevalence ratio: 1.18, 95% CI: 1.05–1.32) were associated with increased risk for congenital diaphragmatic hernia. The 24‐hr, neonatal, and 1‐year survival rates were 93.6%, 79.8%, and 71.2%, respectively. The highest hazard ratio of 17.87 (95% CI: 1.49–213.82) was observed for neonatal mortality among cases associated with chromosomal anomalies and born <37 weeks at < 1, 500 g. Among isolated cases, multiple birth (hazard ratio: 0.41, 95% CI: 0.20–0.86) was associated with decreased 1‐year mortality. Conclusion: Low maternal education and multiple birth may be linked to congenital diaphragmatic hernia. The trends in prevalence, epidemiologic correlates, and predictors of early survival can differ between congenital diaphragmatic hernia subtypes—isolated, multiple, and chromosomal.© 2018 Wiley Periodicals, Inc. © 2018 Wiley Periodicals, Inc.